2010 Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--16754
|View full text |Cite
|
Sign up to set email alerts
|

Cleerhub.Org: Creating A Digital Habitat For Engineering Education Researchers

Abstract: Lafayette. Alejandra's research interests center on how scientists and engineers reason with computing and computational thinking to understand complex phenomena. She is also interested in investigating how scientists and engineers perceive and experience the societal and ethical implications of nanotechnology. Based on her findings her goal is to identify and develop the necessary instructional changes to provide educational frameworks for educators of formal and informal learning environments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Our experience helping build the engineering education research community indicates that it is possible; however, takes time and a concerted effort. 10,11,12,13 Jacqueline R. Roberts, Professor and Chair of Chemistry and Biochemistry, DePauw University…”
Section: Recommendations For the Nsf Improving Undergraduate Stem Education Program Solicitationmentioning
confidence: 99%
“…Our experience helping build the engineering education research community indicates that it is possible; however, takes time and a concerted effort. 10,11,12,13 Jacqueline R. Roberts, Professor and Chair of Chemistry and Biochemistry, DePauw University…”
Section: Recommendations For the Nsf Improving Undergraduate Stem Education Program Solicitationmentioning
confidence: 99%
“…For example, a survey by a project funded to foster a virtual community of engineering education researchers through a web-based hub facility found that responders saw it primarily as a repository providing services and content rather than a real-time connection with the potential for interaction with others or an opportunity to develop a community. 64 Thus there is a challenge in getting faculty to move from an accessing information perspective to a knowledge building one in the virtual world.…”
Section: Participation Of Engineering Faculty Membersmentioning
confidence: 99%